A qualitative study of health care access among African American older adults in a socio-demographically under-resourced region during the COVID-19 pandemic - Ingram, Lucy Annang; Dye, Cheryl; Boger, Heather; Luo, Ye; Hayes, Tara (Frontiers in Public Health, 2022)
Background In the U.S., health inequities experienced by the African American community, specifically among those ages 65 and older, have been well-documented in research literature. Alongside the findings regarding disparities in disease prevalence and management, researchers have also highlighted disparities in health care access. Despite recent evidence of health inequities experienced by African Americans during the COVID pandemic, there is little research on the lived experience of this group in this critical time, health care access challenges that may be exacerbated by the pandemic, and the community's outlook for the future in addressing health disparities. Methods We conducted a qualitative study of African Americans to gather their perspectives about access to health care, particularly during the COVID-19 pandemic. Study participants consisted of African Americans, ages 50–85 years, who spoke English as their primary language, who resided in one of 17 counties in South Carolina that represent a region of the State known as the corridor of economic disadvantage. Results Forty-seven telephone interviews were conducted. While research has shown that certain populations experienced health care access disparities during the early COVID pandemic, these disparities did not appear to be exacerbated in our sample. However, participants noted an increase in the use of telehealth, and identified challenges to using this technology. Participants made recommendations about how to address disparities in health care access in their communities. Conclusion Our qualitative approach was useful in obtaining perspectives about access to health care during the COVID-19 pandemic from African American older adults. Continued research with older African Americans, particularly those in under-resourced communities are warranted to further elucidate these findings.